Interactive media based on project-based learning using Lumi Education for IPAS subjects in 4th-grade elementary school - Yulia, Zikkrillah Nur Miftakhul Laili; Triwahyudianto, Triwahyudianto; Kumala, Farida Nur; Aiman, Wan Muhammad (Journal of Environment and Sustainability Education, 2025)
This research is motivated by the needs of fourth-grade students of SDN 5 Pandesari who tend to be passive and have low learning motivation, thus affecting the achievement of IPAS learning. The purpose of this study is to describe the development process, determine the validity, practicality, and effectiveness of PjBL-based interactive media using the Lumi Education application. This type of research is Research and Development (R&D) which uses the ADDIE development model as the basis for product development. The results in this study indicate that PjBL-based interactive media using the Lumi Education application: 1) valid for use in IPAS learning with a percentage of 96% from media experts with the category "Very valid", 92% from material experts with the category "Very valid", and 88% from linguists with the category "Very valid". 2) practical, with the acquisition of a percentage from teachers of 89% with the category "Very Practical", a limited trial of 86% with the category "Very Practical", and a broad trial of 87% with the category "Very Practical". 3) effective, with an N-gain score of 0.62 with a treatment effectiveness category of "Moderate". Based on these results, it can be concluded that this PjBL-based interactive media using the Lumi Education application is valid and practical for use in learning IPAS grade IV.